Individualization in China under Compressed and Contradictory Modernity - Shi Yunqing (Temporalités)
Because of its unprecedented speed and scale, urbanization in China during the 1990s is one of the most representative fields in which to explore compressed modernity considering East Asian experiences. This article focuses on a collective litigation including 10,357 people suing the local government for the infringements on their property rights and citizenship during that period of urbanization. To make this massive movement possible under an authoritarian state, a new type of state-individual relationship was created, and a selection mechanism applied to the traditional, subordinate state-individual relationship and the modern, egalitarian state-individual relationship was constructed by the activists. The grassroots development of a strategic use of the law is the key to understanding how this selection mechanism was created. Activists distinguished multiple facets of “law”—literal law, symbolic law and practical law–to conceptualize the new egalitarian relationship through self-empowerment, in order to set the necessary preconditions for protesting, by segmenting the traditional state and to mobilize the network of participation by drawing upon the socialist memory of the “movement to popularize legal knowledge”. The selection mechanism described in this article could be considered as the response from individuals to the state during a time of transformation and shows the implication of temporality in the push and pull between individual rights and government overall control connected to the new and old systems. Tensions exist in this selection mechanism, and a paradox lies in the fact that the struggle for this egalitarian relationship should be based on the precondition that the subordinate relationship be internalized. By analyzing this complex process, this article points to China’s special social-historical process as it heads into modernity in an incremental and continuous way within such a short and compressed period of time, and also tackles the theoretical discussion of individualization from an East Asian perspective.